Peran strategi promosi dan kualitas pelayanan dalam menentukan keputusan pembelian properti di PT Binangun Karya Mandiri studi kasus Perumahan Mutiara Puri Harmoni 3 - Anggita, Vina Tri; Handayani, Eva Mayfa (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2026)
This study aimed to analyze the role of promotional strategies and service quality in influencing property purchase decisions at PT Binangun Karya Mandiri. The background of this research was based on the growing demand for affordable housing in Indonesia, particularly subsidized homes, accompanied by challenges in market competition and the limitations of marketing strategies in the digital era. This study employed a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. The results of the study indicated that promotional strategies combining the use of digital and conventional media remained effective in attracting the attention of potential consumers, although improvements were needed in terms of timing and content relevance. On the other hand, service quality encompassing reliability, responsiveness, assurance, empathy, and tangible evidence proved to play a significant role in building consumer trust and comfort during the purchasing process. These findings emphasized that the success of property marketing is not only determined by product quality, but also by the effectiveness of promotional communication and the quality of services provided to consumers.